Approaches to spread, scale-up, and sustainability - Papoutsi, Chrysanthi 1984- (Cambridge University Press, 2024)
Few interventions that succeed in improving healthcare locally end up becoming spread and sustained more widely. This indicates that we need to think differently about spreading improvements in practice. Drawing on a focused review of academic and grey literature, the authors outline how spread, scale-up, and sustainability have been defined and operationalised, highlighting areas of ambiguity and contention. Following an overview of relevant frameworks and models, they focus on three specific approaches and unpack their theoretical assumptions and practical implications: the Dynamic Sustainability Framework, the 3S (structure, strategy, supports) infrastructure approach for scale-up, and the NASSS (non-adoption, abandonment, and challenges to scale-up, spread, and sustainability) framework. Key points are illustrated through empirical case narratives and the Element concludes with actionable learning for those engaged in improvement activities and for researchers. This title is also available as Open Access on Cambridge Core.